Relationships of procrastination with smartphone addiction, social media addiction, academic motivation and self-control in communication - Vyrvich, Anastasiya Ch.; Sheinov, Viktor P. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article presents the results of the study of the relationship between procrastination and smartphone addiction, social media addiction, academic motivation, and self-control in communication. Positive relationships between procrastination and smartphone addiction, social media addiction, self-control in communication, as well as introjected and external motivation were revealed which means a negative relationship between procrastination and academic motivation. It is noted that the positive relationship between procrastination and self-control in communication obtained in this stu-dy is a new result.
Keywords: procrastination; smartphone addiction; social media addiction; academic motivation; self-control; self-control in communication